The lady of the lakes [large type] : the love story of Sir Walter Scott - Kilpack, Josi S. (Thorndike Press, a part of Gale, a Cengage Company, 2018)
One is his first love. The other is his best love. Which will be his true love? Walter Scott has three passions: Scotland, poetry, and Mina Stuart. Though young and from a different station in society, she is the sunshine of his soul. Yet it's hard for Mina to know if she is only dazzled by Walter's flattery. When she meets charming William, her heart is challenged. Then, one windy morning in the lake country, Walter meets Charlotte. Passion and promises collide as all must decide the course for their futures.